A case report of typical well-differentiated papillary mesothelial tumor diagnosed by internal thoracoscopy and literature review - Guo, Jian; Lv, XiaoHui; Zhang, Wei; Dong, Fang; Li, Lei; Liu, Juan; Li, Bing (Frontiers in Oncology, 2024)
We report a case of well-differentiated papillary mesothelial tumor (WDPMT) diagnosed using internal thoracoscopic biopsy in a patient who has suffered from recurrent pleural effusions for over 35 years together with a history of elevated CA125. We hope to provide a case for the diagnosis of this rare benign and preinvasive pleural tumor and recommend that internal thoracoscopy may be a good choice in these recurrent pleural effusion patients especially for those minimal lesions not easily detected using CT scan.